The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/hc.21445
|View full text |Cite
|
Sign up to set email alerts
|

Group 13 metal carbochalcogenoato complexes: Synthesis, X‐ray structure analysis, and reactions

Abstract: A series of alkali metal tetrakis(carbochalcogenoato)‐gallates and ‐indates M[M′(EOCR)4](solv.) (M = alkali metal; M′ = Ga, In; E = S, Se) and tris(carbodithioato)aluminum, ‐gallates and ‐indates M′ (SSCR)3 (M′ = Al, Ga, In) were prepared by the reactions of alkali metal carbochalcogenate with metal trihalogenides (M′X3; M′ = Al, Ga, In; X = Cl, Br) and by those of piperidinium carbodithioates or carbodithioic and carboselenoic acids with M′X3, respectively. An X‐ray molecular structure analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previously, we have investigated the stepwise route to alkyl/chloro-gallium donor-functionalized alkoxides from the reactions of gallium chloride with lithium dimethylamide and lithium hexamethyldisilazide, including an in-depth crystal structure analysis. Other works report of functionalization through ethers, and more recently, even thioethers to deposit oxysulfide thin films. , Gallium/copper mixed-metal thiolate compounds, used for potential gallium copper sulfide materials, were shown to have simple room-temperature NMR spectra; however, low-temperature NMR studies revealed the complex dissociative mechanisms that these precursors undergo in solution. This information can be used to understand thermolytic pathways during deposition to the target material.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have investigated the stepwise route to alkyl/chloro-gallium donor-functionalized alkoxides from the reactions of gallium chloride with lithium dimethylamide and lithium hexamethyldisilazide, including an in-depth crystal structure analysis. Other works report of functionalization through ethers, and more recently, even thioethers to deposit oxysulfide thin films. , Gallium/copper mixed-metal thiolate compounds, used for potential gallium copper sulfide materials, were shown to have simple room-temperature NMR spectra; however, low-temperature NMR studies revealed the complex dissociative mechanisms that these precursors undergo in solution. This information can be used to understand thermolytic pathways during deposition to the target material.…”
Section: Introductionmentioning
confidence: 99%